INTERNATIONAL STUDENTS’ PERCEPTIONS OF DIGITAL TECHNOLOGY USE IN PKPBI AT UIN MALANG - Amnan, Amira Aulia; Ni'am, Hoirotun; Suffyany, Soleh; Rohmana, Wahyu Indah Mala (Faculty of Teacher Training and Education, English Department, UNISKA, Kediri, 2026)
The rapid advancement of technology in the digital era has influenced various fields, including higher education. Most universities have integrated technology as a medium of instruction, and Universitas Islam Negeri (UIN) Maulana Malik Ibrahim Malang is no exception. This study aims to explore international students’ perceptions of the use of digital technology in English language learning in Special English Language Program (PKPBI) at UIN Malang. This research employs a descriptive qualitative approach with data collected through structured interviews with 5 international students. The study is grounded in the Technology Acceptance Model (TAM) proposed by Davis (1989), which consists of two key components: Perceived Usefulness and Perceived Ease of Use. This research also refers to a previous study conducted by Hidayat et al. (2022), titled “Digital technology supporting English learning among Indonesian university students,”. The present study extends their research by focusing on international students at UIN Malang. Preliminary findings indicate that international students have a positive perception of the use of digital technology in PKPBI learning at UIN Malang.